Family business succession in different national contexts: a fuzzy-set QCA approach - Porfírio, José (2019)
Family business succession is a key topic that has attracted considerable attention from researchers, especially in the last decade. Most research, however, is based on case studies with limited applicability and fails to present comparisons across international contexts that highlight di erences in succession processes. We apply expectation states theory to analyze a sample of 128 observations in two Southern European countries, Portugal and Greece. We study configurations of successors’ characteristics, family business characteristics, the existence (or absence) of a succession plan, and successors’ motivation to succeed. Our aim is to reveal how these issues a ect successors’ perceptions of preparation for succession using fuzzy-set qualitative comparative analysis (fsQCA). Family businesses are a dominant organizational form all over the world, and succession issues are critical for the sustainability of family businesses. Our findings suggest that di erent configurations of conditions influence successors’ perceptions of preparation for family business succession. Moreover, we verify the influence of cultural di erences on these processes. This research helps fill a gap in the literature, showing the role of a set of characteristics in successors’ perceptions of preparation for family business succession. Our conclusions provide insight into the types of policies that can promote successful family business succession.